Lactoferrin combined with Coenzyme Q10 ameliorate sarcopenia in an aging mouse model induced by D-galactose - Wenbin Wu; Yinhua Zhu; Yanan Fu; Hongfei Xing; Xinlu Guo; Jichao Xu; Wenhui Hu; Mingyang Cui; Jiaxin Shi; Ling Li; Weiwei Wang; Peng An; et al. (PLoS ONE, 2025)
Sarcopenia is an age-related condition with a slow and prolonged decrease in muscular mass, strength, and function. As the population ages, the frequency of sarcopenia rises, and aggressive prevention methods and effective treatment options are in urgent need. Here, we explore the hypothesis that nutritional interventions can ameliorate skeletal muscle aging in mice affected by sarcopenia, and the aforementioned hypothesis was validated through histopathological characterization and behavioral experiments. The model group exhibited reduced muscle mass (Lean Mass, GAS Index), muscular strength (Maximum Limb Muscle Strength), and muscular function (Exhaustion Time, Inverted Grid Time), along with increased fat content and smaller myofiber size compared to the control group. Treatments with lactoferrin and CoQ10, both individually and in combination, enhanced muscle indices and facilitated muscle tissue regeneration, with the combined treatment showing the most significant improvement. Research further shows that Lactoferrin and CoQ10, whether administered alone or in combination, were discovered to restrain the progression of sarcopenia by inhibiting both protein metabolism and mitochondrial energy metabolism, and compared to groups treated with lactoferrin or CoQ10 alone, the combined treatment demonstrated varying degrees of improvement across all evaluated metrics, such as Lean Mass (2.273 ~ 5.365%), Fat Mass (−1.058 ~ −0.359%), GAS index (0.259 ~ 0.335%), Maximum Limb Muscle Strength (6.83 ~ 53.498 g), Inverted Grid Time (563 ~ 859 s), Exhaustion Time (386 ~ 468 s).